Substitution of Maggot Flour (Hermetia Illucens) in Feed on The Performance of Male Peking Duck - Firmansyah, Muhammad Fandy; Yakin, Engkus Ainul (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Black Soldier Fly (BSF) maggot meal is one of the sustainable protein sources that need to be investigated due to the rising expense of conventional protein feed. This study aimed to evaluate the effect of BSF (Hermetia illucens) maggot meal substitution in rations on the growth performance of male Peking broiler ducks and to determine the optimal level of use. A Completely Randomized Design (CRD) with three treatments and four replications (four ducks per experimental unit) was the research methodology. Grower phase ducks were treated with P0 (0% maggot meal), P1 (10% maggot meal), and P2 (20% maggot meal). Feed consumption, body weight increase (PBB), and feed conversion ratio (FCR) were among the metrics noted. With an average intake of 45.00 g/head/day, statistical analysis revealed that maggot meal substitution had no significant effect (P>0.05) on feed consumption. On daily body weight gain, however, there was a significant influence (P<0.05), with P1 attaining the maximum growth rate of 17.65 g/head/day. Regarding feed efficiency, although statistically the FCR values ​​between treatments did not show a significant difference (P=0.056), the P1 treatment numerically recorded a lower conversion rate (2.37) compared to the control (3.07). This study concluded that the use of maggot flour up to 10% (P1) has the potential to increase growth rates without compromising feed palatability. These findings provide practical implications for livestock farmers in optimizing production efficiency through the use of local feed ingredients based on organic waste.